PENINGKATAN KINERJA SISTEM PROPULSI KAPAL PENANGKAP IKAN TRADISIONAL TYPE PURSEINE 30 SD 90 GT MENGGUNAKAN SISTIM PROPULSI HYBRID - Ridwan, Mohd (Vocational School Diponegoro University, 2011)
Mohd Ridwan, in this paper explain that traditional fishing vessels built in the shipyard of the people is a cultural heritage which needs to be conserved, and empowered through the application of ship science and technology to build fishing boats for fishermen of all types, shapes and sizes of ships, equipped with fishing technology. Repairs to the feasibility of traditional fishing vessels to sail like stability, ship construction needs to be done. Similarly, his case should be applied to ship propulsion technology that remained operational needs based on size of vessel forms and types of fishing vessels. The design of an appropriate propulsion can provide benefits in the form of operational cost savings by more than 10% through the use of hybrid propulsion systems. Hybrid propulsion system is a mix of main engine (motor fuel or gas fuel MDO) with electric motor and propeller to suit the use of hull form and ship propulsion systems (matching the propeller and engine) is at the core of this concept in this article and next to be research. Besides these traditional ship the product to be supported primarily by imposing government standards for a fishing vessel, for fishermen as users can easily calculate the economic value of investment will they planted in fishing effort at sea.Â Keywords : Fishing Boat Traditional, Hybrid Propulsion, Main Engine, Propeller, Operatinal Cost.